Rapid apoptosis in the pulmonary vasculature distinguishes non-metastatic from metastatic melanoma cells - Kim, J; Wong, C; Goldsmith, J; Song, C; Fua, W; Allion, M; Herlyn, M; Al-Mehdi, AB; Muschel, R (2004)
The presence of metastases indicates an ominous prognosis in patients with malignancies, yet the factors that distinguish metastatic from non-metastatic tumors remain poorly understood. Here we pursued the hypothesis that apoptosis in vivo would distinguish metastatic cells from non-metastatic cells and developed a novel method for observation of apoptosis induction in living cells. One hour after the infusion of metastatic or non-metastatic human melanoma or transformed rat embryo fibroblasts, arrest of tumor cells in the pulmonary vasculature was equivalent. In order to demonstrate the induction of apoptosis in living cells, we observed the translocation of cytoplasmic BAD-GFP fusion proteins to the mitochondria during apoptosis. Microscopic observation of the tumor cells transfected with BAD-GFP in isolated lung preparations after intravenous injection into nu/nu mice revealed translocation of BAD-GFP in many more of the arrested, non-metastatic melanoma or transformed rat embryo cells over 4-24 h than of the metastatic cells. TUNEL staining confirmed enhanced apoptosis by non-metastatic tumor cells after injection in vivo. Metastatic melanoma cells or metastatic embryo fibroblasts were better able to negotiate the barrier of survival in the circulation after pulmonary arrest than non-metastatic cells confirming the hypothesis that susceptibility to apoptosis after arrest in the pulmonary vasculature distinguishes metastatic from non-metastatic cells and introducing a new assay for in vivo induction of apoptosis. © 2004 Elsevier Ireland Ltd. All rights reserved.